Factors that affect corporate performance on the Environmental part of ESG in the Czech Republic - Xu, Fahua; Tyll, Ladislav; Balogh, Ivan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This master’s thesis aims to investigate the factors that affect corporate environmental performance disclosure in the Czech Republic. For this purpose, the research is constituted of hypotheses, data collection, model selection and data analysis. Hypotheses are established based on the reviewed literature. The sampled dataset contains 200 Czech companies that meet at least two of the requirements for large companies by Corporate Sustainability Reporting Directive. Tobit model is employed for the purpose of data analysis as it is a valuable tool in estimating linear relationships between variables where dependent variable is either censored or truncated. The data analysis then reveals that, being listed on a stock exchange, media coverage, assurance provided Big4, and operation in foreign markets have significant positive impacts on environmental disclosure. Profitability is negatively related with the environmental disclosure. Contrary to prior researches, no statistically significant relationship was observed between environmental disclosure and both variables of sensitive industry and company size. Finally, explanation based on the reviewed literature, limitation and further research recommendation are provided.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses